Physics Contributionsons BiopSee® – transperineal stereotactic navigated prostate biopsy - Zogal, Pawel; Sakas, Georgios; Rösch, Woerner; Baltas, Dimos (Journal of Contemporary Brachytherapy, 2011)
In the recent years, prostate cancer was the most commonly diagnosed cancer in men. Currently secure diagnosis confirmation is done by a transrectal biopsy and following histopathological examination. Conventional transrectal biopsy success rates are rather low with ca. 30% detection upon the first and ca 20% after re-biopsy. The paper presents a novel system for stereotactic navigated prostate biopsy. The approach results into higher accuracy, reproducibility and unrestricted and effective access to all prostate regions. Custom designed ultrasound, new template design and integrated 2-axes stepper allows superior 2D and 3D prostate imaging quality and precise needle navigation. DICOM functionality and image fusion enable to import pre-operative datasets (e.g. multiparametric MRI, targets etc.) and overlay all available radiological information into the biopsy planning and guiding procedure. The biopsy needle insertion itself is performed under augmented reality ultrasound guidance. Each procedure step is automatically documented in order to provide quality assurance and permit data re-usage for the further treatment. First clinical results indicates success rates of ca. 70% by first biopsies by our approach.